EVALUASI PENGELOLAAN DANA DESA (Studi Pada Desa Di Kota Tual) - Yoga Andriyan; Sofyan Muhamad; Yusron Difinubun; Rahmat Hidayat (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2022)
This research aims to evaluate the management of village funds in Tual City, in order to work together to oversee the government's commitment to implementing the development agenda and national economic equality, especially in the Maluku Province and generally throughout the Republic of Indonesia. As well as being able to learn from the success of Ponggok Village, Polanharjo District, Klaten, Central Java which is a reference village for the use of village funds for other villages in Indonesia. This research uses qualitative data analysis techniques (model of Miles and Haberman, 1998). namely analyzing through data reduction, data presentation (display data), and Conclusion or Data verification (conclusion drawing/verification). Based on the results of the study, it is known that the management of village funds is in accordance with the established standards, namely by using the minister of finance regulation No. 49 of 2016 and Tual mayor regulation No. 1 of 2016. Suggestions that can be given include that the village government in Tual city should increase socialization about the importance of community participation in village community empowerment programs. The village government must prepare a place for selling the results of the creativity of the village community, in addition, to opening market access, so that the creative results of the village community can increase village income and community income.